The virgin warrior : the life and death of Joan of Arc - Taylor, Larissa (Yale University Press, 2009)
"In The Virgin Warrior, Larissa Juliet Taylor paints a vivid portrait of Joan as a self-confident, charismatic and supremely determined figure, whose sheer force of will electrified those around her and struck terror into the hearts of the English soldiers and leaders."--Inside book jacket